Association between 5-HTTLPR and Borderline Personality Disorder Traits among Youth - Hankin, Benjamin; Barrocas, Andrea L.; Jenness, Jessica; Oppenheimer, Caroline; Badanes, Lisa; Abela, John; Young, Jami; Smolen, Andrew (Frontiers in Psychiatry, 2011)
This study provides the first genetic association examination of borderline personality disorder traits (BPD) traits in children and adolescents (ages 9-15) using two independent samples of youth recruited from the general community. We tested the a priori hypothesis that the serotonin transporter promoter gene (5-HTTLPR) would relate specifically to BPD traits in youth. This association was hypothesized based on prior genetic association research with BPD adults and theory positing that emotion dysregulation may be a core risk process contributing to BPD. Youth provided DNA via buccal cells. Both youth and a parent completed self-report measures assessing youth’s BPD traits and depressive symptoms. Results from both Study 1 (N = 242) and an independent replication sample of Study 2 (N = 144) showed that carriers of the short allele of 5-HTTLPR exhibited the highest levels of BPD traits. This relation was observed even after controlling for the substantial co-occurrence between BPD traits and depressive symptoms. This specific association between 5-HTTLPR and BPD traits among youth supports previous genetic associations with adults diagnosed with BPD and provides preliminary support for a developmental extension of etiological risk for BPD among youth.